Bone marrow pathology - Bain, Barbara J.; Clark, David M.; Wilkins, Bridget S. 1959- (Wiley Blackwell, 2019)
The normal bone marrow -- Special techniques applicable to bone marrow diagnosis -- Infection and reactive changes -- Acute myeloid leukaemia, mixed phenotype acute leukaemia, the myelodysplastic syndromes and histiocytic neoplasms -- Myeloproliferative and myelodysplastic/myeloproliferative neoplasms and related conditions -- Lymphoproliferative disorders -- Plasma cell neoplasms -- Disorders of erythropoiesis, granulopoiesis and thrombopoiesis -- Miscellaneous disorders -- Metastatic and non-haemopoietic tumours -- Diseases of bone
Includes bibliographical references and index
Keywords: Knochenmark; Pathologie; Knochenmarkkrankheit; Bone marrow / Histopathology; Bone marrow / Diseases; Bone Marrow Diseases / pathology; Bone Marrow / pathology; Lehrbuch